Effect of mold temperature on properties of hybrid biocomposites from semicrystalline polymers and agro-industrial by-products (2023)
The surface temperature of the mold is a critical processing parameter that significantly influences the quality of composites during injection molding. Therefore, this study aimed to investigate the effect of mold surface temperature on the properties of hybrid biocomposite materials prepared by incorporating polypropylene-PP with agro-industrial by-products such as rice husks-RH and fique powder-FP using co-rotating twin-screw extrusion and injection molding. While this article focuses on PP as the polymeric matrix, the methodology employed in this study can also be applied to investigate the effect of mold surface temperature on the properties of other polymers used in the production of hybrid composites via injection molding as biobased or biodegradable plastics. The mechanical characterization reveals that the utilization of higher mold temperatures and the hybridization of RH and FP result in an increase in the elastic modulus of up to 30% compared to PP. Also, thermal, viscoelastic, morphological, and HDT characterization revealed that higher surface mold temperature led to changes in PP crystallinity, and a better hybrid biocomposites performance. This study highlights the potential of mold surface temperature controlling and agro-industrial by-products hybridization for the design and production of higher quality and sustainable products using injection molding